Student Perceptions on Information and Communication of IAIN Pontianak’s Instagram Social Media - Handes Handes (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to find out the perception of IAIN Pontianak students towards IAIN Pontianak’s Instagram account posts. This study uses qualitative research with a descriptive approach. The purpose of this study is to analyze students’ perception of information and communication on the Instagram social media account of the State Islamic Institute (IAIN) Pontianak, namely, iainptk_official. Data collection techniques use interviews, observations, and documentation. The results of this study show that students are not interested in posting information on iainptk_official accounts. This is because the posts that are made are not routine and are posted once in large numbers. This results in them having difficulty finding the latest information obtained through their Instagram account. This research has limitations in qualitative research methods and in a relatively small number of informants. Thus, the next research can conduct a survey of all IAIN Pontianak students with quantitative research.